Analysis of football referees injuries - literature review - Mańko, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction and purpose: According to the literature, injuries are defined as the result of the action of significant energy, causing dysfunction and anatomical-physiological changes. In the case of football referees, sports injuries occur during physical exertion in the form of matches and training sessions. As a result, various injuries occur, both on the pitch and during arduous training. They often take place as the aftermath of summed micro-injuries. Properly early detection and analysis of these signals helps to heal the damage and to avoid a longer break from activity, which would inevitably result in a serious injury. The aim of this study is to analyze the most common injuries and their risk factors in football referees on the basis of the current literature. Description of the state of knowledge: 9 research papers from the last twelve years (2009-2021) containing the above-mentioned keywords have been qualified for this review. Based on the above works, it is possible to determine when and how often injuries occur among referees, and what areas of the body are injured. Due to the multifactorial etiology of injuries and heterogeneous diagnostic systems, which would constitute a standardized research tool, it is difficult to say unequivocally what is the greatest cause of an injury. Conclusions: 1) Injuries among referees at different levels of the game occur more often due to the match load than the training load. 2) Muscle injuries were the most common, but there was no indication of a tendency towards the exact location of the injury, which requires further research.